CO2 Sequestration (IntechOpen, 2020)
This book discusses different strategies that can be adopted by agriculture and industry to enhance CO2 sequestration and reduce the impacts of global warming and climate change. Written by researchers from different fields, chapters cover such topics as the management of agricultural systems with the implementation of agronomic practices that can reduce greenhouse gas emissions and increase soil carbon stocks, the technology of adsorption on activated carbon from low-cost raw material, and the effective methods of carbon capture and storage, among others. This volume is a useful reference for the general public, undergraduate and graduate students, and researchers who aim to deepen their knowledge of those topics.